O ENSINO DE FÍSICA NUCLEAR E SUAS APLICAÇÕES NO CONTEXTO DA SOCIEDADE CONTEMPORÂNEA - Peron, Josicarlos (2016)
Due to the advance of Modern Science, society is immersed in a reality of technological innovations. This way, the importance of the debate about the influence of Science and Technology on the life of the population becomes fundamental. Therefore, we chose a discussion related to Nuclear Physics and its applications, since, nuclear accidents, military tests, improvements in medical treatment techniques, has gained relative prominence in recent years. In this reality,the school environment plays a relevant role in the mediation of the debate, since it is the school´s competence to formalize the knowledge acquired by the student through, mainly, common sense. Based on the analysis of dialogues with some professors of High School Physics, a research carried out on the internet of programs and suggestions to approach the Nuclear Physics in the school context and of the didactic books adopted by the Public Schools of the State of Paraná, distributed through the National Textbook Program (PNLD), it was verified that topics related to Nuclear Physics, although its approach is considered relevant by many teachers, still occurs in a very restricted way, mainly due to the complexity dealing with the phenomena, An extensive program of physics in relation to the workload, as well as a lack of preparation on the teacher´s part, which generates insecurity in the approach of such contents. This way, as an integral part of this work, an educational product was developed, based on a careful didactic transposition on topics of Nuclear Physics, aiming at assisting student in training process, especially in what concerns a critical position against the use of nuclear energy. The educational product proposes an approach within a historical, social, cultural and political contextualization, as proposed by the CTS movement, since Science is the fruit of a human evolution, and can not be neutral. The proposal was applied in a high school class, in the Training Course of Early Childhood Teachers and Initial Years of Elementary School, in the Integrated modality, of the Barão de Antonina State College, Rio Negro, Paraná, from November to December 2015.